Optimal CSD reshaping towards T2S - Fabien Mercier; Stephan Sauer (European Central Bank (ECB), 2013)
T2S is the single and harmonised IT platform for securities settlement in central bank money developed by the Eurosystem to promote integration in the European post-trading industry, and will go live in 2015. CSDs joining T2S are thus faced with the decision problem of determining to which degree they should reshape, that is, adapt their own IT infrastructure, human resources and business strategy to T2S. A more complete reshaping entails higher immediate fixed costs, but allows to benefit the most from the cost-reduction allowed by T2S. In this article we use a game theoretic approach to model the strategic choice of the CSDs. We then derive several results from this model. In particular, we give closed-form solutions for the degree of optimal reshaping and the optimal prices set in the unique equilibrium if the time-horizon is finite. In case of an infinite horizon we give a sufficient and necessary condition for the existence of another subgame perfect Nash equilibrium in which CSDs continually delay the decision to reshape. We argue this equilibrium is not robust and provide a condition under which a given CSD will always reshape, whatever the other CSDs' strategy. We note that by adjusting the cost function and the interpretation of the reshaping parameter, the same game theoretic framework can be used to model the decision to join or not to join T2S.
Keywords: G10; G20; L11; 330; adaptation costs; Securities settlement; TARGET2-Securities (T2S); Bargeldloser Zahlungsverkehr; Internationaler Zahlungsverkehr; IT-Infrastruktur; Europa